2020
DOI: 10.1088/1555-6611/ab6d65
|View full text |Cite
|
Sign up to set email alerts
|

High-energy hundred-picosecond fiber-solid hybrid laser and its application in laser-induced damage in PIN photodiode

Abstract: We report on a home-made high-energy hundred-picosecond fiber-solid hybrid laser system, which consists of a high-stability all-fiber seed source and a high-energy quasi-continuouswave laser diode side-pumped Nd:YAG regenerative amplifier. With this system, pulse energy of 4 mJ and pulse duration of 302 ps have been achieved at 500 Hz repetition rate. The highenergy picosecond pulses of this laser amplifier are used for the experiments of laser-induced damage in the PIN photodiode. Detection signals and damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…To further corroborate the plasma generation under this hundred-picosecond laser irradiation, in accordance with the hydrodynamic theory, three first-order quasi-linear partial differential equations were solved separately using the finite element method [43,44]. Accordingly, we obtained the two-dimensional spatial distribution of the free electron concentration within the 100 ps time range, as demonstrated in Figure 12.…”
Section: The Theoretical Simulation Of Hundred-picosecond Laser Ablationmentioning
confidence: 92%
“…To further corroborate the plasma generation under this hundred-picosecond laser irradiation, in accordance with the hydrodynamic theory, three first-order quasi-linear partial differential equations were solved separately using the finite element method [43,44]. Accordingly, we obtained the two-dimensional spatial distribution of the free electron concentration within the 100 ps time range, as demonstrated in Figure 12.…”
Section: The Theoretical Simulation Of Hundred-picosecond Laser Ablationmentioning
confidence: 92%
“…This block diagram is divided into three parts-transmitter side, transmission channel and receiver side. The transmitter consists of three basic components-pseudorandom bit sequence generator that generates the bits in random manner, optical source for converting electrical pulses to optical pulses and MZ modulator for transmission of those pulses to longer distances [22,23]. The transmission channel consists of SMF along with a combination of UFBG and EDC for mitigating the effect of dispersion before it reaches the receiver.…”
Section: System Modellingmentioning
confidence: 99%
“…Wang et al utilized a picosecond laser to irradiate a PIN detector and observed that the surface damage of the PIN photodiode can be analyzed through deep melting transients and plasma motion. 8 A study conducted by Meng et al investigated the transient signal broadening of silicon-based photodiodes when exposed to nanosecond laser radiation. It was observed that the silicon-based PIN detector exhibited nonlinear saturation following laser irradiation, accompanied by a significant increase in response time.…”
Section: Introductionmentioning
confidence: 99%